Prioritizing Marketplace Features in Indonesian E-Commerce Platforms Using the Kano Model: Evidence from Shopee, Tokopedia, and Lazada - Fahrobby Adnan; Januar Adi Putra; Shyfanaya Aulia; Dwi Jannah Oktavia; Muhammad Ahsan Hilmi (Politeknik Siber Cerdika Internasional, 2026)
Background: Indonesia’s e-commerce sector is rapidly growing, with transactions reaching USD 82 billion in 2023 and expected to exceed USD 160 billion by 2030. Despite this expansion, retaining customers remains challenging, as platforms often invest in new features without systematically analyzing customer needs. Objective: To identify and prioritize customer-desired features on Shopee, Tokopedia, and Lazada using the Kano Model combined with the Satisfaction Index and Self-Stated Importance, thereby providing actionable recommendations for platform development. Methods: This research utilizes the Kano Model to analyze customer needs on the Shopee, Tokopedia, and Lazada market places, which were identified as the three most popular marketplaces based on the results of customer loyalty calculations using the Net Promoter Score (NPS). Results: The findings confirmed that Shopee, Tokopedia, and Lazada are the top three marketplaces in Indonesia. This research, using the Kano Model, aims to determine feature categorizations and prioritize features for development based on the results of the Satisfaction Index and Self-Stated Importance calculations. According to the Kano Model, 14 features of Shopee are categorized as Attractive. Meanwhile, 11 features of Tokopedia are categorized as Attractive, One-dimensional, and Indifferent. In addition, 13 features of Lazada are categorized as Must-be, One-dimensional, Attractive, and Indifferent. Conclusion: The Kano Model effectively distinguishes feature priorities across marketplaces. Developers should focus on Attractive features for differentiation while maintaining Must-be features. Recommended strategies include Shopee social commerce; Tokopedia service integration; and Lazada payment ecosystem reliability. This approach offers a replicable framework for managing digital platform features.